2016
DOI: 10.1021/acs.jafc.6b01065
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Previously Unobserved Stereoisomers of Thujone in the Essential Oil and Consumable Products of Sage (Salvia officinalis L.) Using Headspace Solid-Phase Microextraction–Gas Chromatography–Mass Spectrometry

Abstract: The discovery of the (+)-α-thujone and (-)-β-thujone stereoisomers in the essential oil of sage (Salvia officinalis L.) and dietary supplements is documented for the first time. The detection was accomplished using a chiral resolution protocol of racemic α-/β-thujone on headspace solid-phase microextraction-gas chromatography-mass spectrometry. Because the previously unreported stereoisomers, (+)-α-thujone and (-)-β-thujone, are not commercially available, a three-step synthesis of racemic thujone from commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Plant secondary metabolites having the potential to treat a variety of diseases are divided into many classes such as flavonoids, phenolic acids, phenolic glycosides, unsaturated lactones, phenylpropanoids, lignins, terpenoids, and steroids. These valuable compounds have many applications in the cosmetic, food, and pharmaceutical industries (Banerjee & Bonde, 2011;Williams, Yazarians, Almeyda, Anderson, & Boyce, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites having the potential to treat a variety of diseases are divided into many classes such as flavonoids, phenolic acids, phenolic glycosides, unsaturated lactones, phenylpropanoids, lignins, terpenoids, and steroids. These valuable compounds have many applications in the cosmetic, food, and pharmaceutical industries (Banerjee & Bonde, 2011;Williams, Yazarians, Almeyda, Anderson, & Boyce, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no chiral characterization of above mentioned TmEOs has been reported [ 2 – 11 ]. However, such data are important for quality assurance, since they help to assess either the genuineness or possible adulteration of the EOs, as well as their origin [ 12 ]. Furthermore, the information is required to use TmEOs as a natural source of pure enantiomers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards the chiral characterization of SoEOs, only a few studies have reported the enantiomeric distribution of the principal components . The chiral distribution of the main compounds counts as a quality assurance marker to determine both the authenticity and the applicability of a given EO.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the chiral characterization of SoEOs, only a few studies have reported the enantiomeric distribution of the principal components. [26] [27] The chiral distribution of the main compounds counts as a quality assurance marker to determine both the authenticity and the applicability of a given EO. An adulterated EO may contain racemic mixtures of the main compounds, obtained by chemical synthesis, making it cheaper than the corresponding EOs with their chiral natural compounds.…”
Section: Introductionmentioning
confidence: 99%